Prophylactic antiviral therapy for hepatitis B virus surface antigen‐positive patients with diffuse large B‐cell lymphoma treated with rituximab‐containing chemotherapy. Issue 5 (18th March 2021) - Yamauchi, Nobuhiko; Maruyama, Dai; Choi, Ilseung; Atsuta, Yoshiko; Sakai, Rika; Miyashita, Kazuho; Moriuchi, Yukiyoshi; Tsujimura, Hideki; Kubota, Nobuko; Yamamoto, Go; Igarashi, Tadahiko; Izutsu, Koji; et al.
Abstract: We conducted a nationwide retrospective analysis of 116 hepatitis B virus (HBV) surface antigen (HBsAg)‐positive patients with diffuse large B‐cell lymphoma (DLBCL) and 278 HBsAg‐negative patients with DLBCL, as a control cohort, who received rituximab‐containing regimens as an induction chemotherapy at 30 Japanese medical centers between January 2004 and December 2014. Hepatitis was defined as an absolute serum alanine aminotransferase (ALT) level of ≥100 U/L. HBV reactivation‐related hepatitis was defined as hepatitis with an absolute serum HBV DNA level of ≥3.3 log IU/mL or an absolute increase of ≥2 log compared with the baseline value. HBsAg‐positive patients were divided into three groups based on anti–HBV prophylactic therapy: no nucleos(t)ide analogue (non–NA, n = 9), lamivudine (LAM, n = 20), and entecavir (ETV, n = 87). The 4‐year cumulative incidence (CI) of hepatitis in HBsAg‐positive and HBsAg‐negative patients was 21.1% and 14.6% ( P = .081), respectively. The 4‐year CI of HBV reactivation‐related hepatitis was higher in HBsAg‐positive patients than in HBsAg‐negative patients (8.0% vs 0.4%; P < .001). Among HBsAg‐positive patients, the 4‐year CI of HBV reactivation‐related hepatitis was the highest in the non–NA group (33.3%), followed by the LAM (15.0%) and ETV (3.8%) groups ( P < .001). Of note, 3 non–NA patients (33%) and 1 LAM patient (5%) (but no ETV patients) died due to HBV hepatitis. Based on Cox multivariate analysis, HBsAg positivity was not associated with poor overall survival. Prophylactic use of ETV would reduce the occurrence of HBV reactivation‐related hepatitis and mortality in HBsAg‐positive DLBCL patients receiving rituximab‐containing chemotherapy. Abstract : Prophylactic use of entecavir reduced HBV‐related hepatitis and mortality in HBsAg‐positive DLBCL treated with R‐chemotherapy. The 4‐year overall survival rate in HBsAg‐positive DLBCL patients receiving prophylactic entecavir was similar to that in HBsAg‐negative DLBCL.